2020
DOI: 10.3389/fmicb.2020.01145
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Apoptosis by Enteroviruses

Abstract: Enterovirus infection can cause a variety of diseases and severely impair the health of humans, animals, poultry, and other organisms. To resist viral infection, host organisms clear infected cells and viruses via apoptosis. However, throughout their long-term competition with host cells, enteroviruses have evolved a series of mechanisms to regulate the balance of apoptosis in order to replicate and proliferate. In the early stage of infection, enteroviruses mainly inhibit apoptosis by regulating the PI3K/ Akt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 132 publications
(152 reference statements)
1
9
0
Order By: Relevance
“…Enteroviruses (EV) are positive-sense RNA viruses in the order Picornavirales [ 68 ] that have been well studied in relation to apoptosis. EV can inhibit apoptotic pathways in the early stage of infection but induce apoptosis to release viral progeny in the late stage of infection [ 69 ]. Therefore, it is reasonable to suggest that the apoptosis mechanism may be used to destroy the cell and release DWV virus particles in newly emerged adult bees and further induce immune responses within the host [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Enteroviruses (EV) are positive-sense RNA viruses in the order Picornavirales [ 68 ] that have been well studied in relation to apoptosis. EV can inhibit apoptotic pathways in the early stage of infection but induce apoptosis to release viral progeny in the late stage of infection [ 69 ]. Therefore, it is reasonable to suggest that the apoptosis mechanism may be used to destroy the cell and release DWV virus particles in newly emerged adult bees and further induce immune responses within the host [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…To efficiently replicate, cardiogenic viruses such as enteroviruses inhibit apoptosis signaling at the beginning of viral infection. In later stages, the focus shifts to viral release, so enteroviruses manipulate the host cell towards apoptosis [ 113 ]. PVB19 utilizes its nonstructural protein NS1 to trigger cell-cycle arrest to induce apoptosis in endothelial cells in the late viral cycle [ 33 , 114 ].…”
Section: Programmed Cell Deathmentioning
confidence: 99%
“…by inhibiting apoptosis in order to efficiently replicate inside the host cells in early stage of infection. In later infection phases enteroviruses induce apoptosis to facilitate the release of the virus via cell lysis [123,124].…”
Section: Enteroviruses (Cvb3)mentioning
confidence: 99%
“…Agol et al observed a pro-apoptotic phase at the very early stage of infection, followed by an anti-apoptotic stage and another switch to pro-apoptotic signaling in the late stage of infection [165]. By sequentially inhibiting or activating cell signaling, viruses can regulate apoptosis at different stages of infection [123]. One way to control this is by gradually increasing cytosolic Ca 2+ levels through the expression of viroporins, which is initially pro-survival at moderate Ca 2+ levels, but promotes apoptosis at later stages with high cytosolic Ca 2+ concentrations.…”
Section: Enteroviruses (Cvb3)mentioning
confidence: 99%